2018
DOI: 10.3390/molecules23102536
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Honokiol Analogs and Their Evaluation for Activity on the Norepinephrine Transporter

Abstract: In traditional Asian medicinal systems, preparations of the root and stem bark of Magnolia species are widely used to treat anxiety and other nervous disturbances. The biphenyl-type neolignans honokiol and magnolol are the main constituents of Magnolia bark extracts. In the central nervous system, Magnolia bark preparations that contain honokiol are thought to primarily interact with γ-aminobutyric acid A (GABAA) receptors. However, stress responses inherently involve the noradrenergic system, which has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The presence of these neolignans in the other species of the genus Magnolia , including M. officinalis , M. obovata , and M. virginiana , has led to the use of supplements prepared from these extracts as anti-depressants, analgesics, aphrodisiacs, and appetite suppressants or stimulants [ 17 ]. Earlier studies [ 24 ] have indicated that 1 and 2 could potentiate γ-aminobutyric acid A (GABA A ) receptors and could act as positive allosteric modulators (PAMs); however, these neolignans have shown no direct interaction with the norepinephrine transporter [ 25 ]. In 2004, Kong et al, evaluated the MAO inhibitory potential of 2 and 3 using rat brain mitochondria; however, no significant rat brain MAO inhibitory activity was noted [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these neolignans in the other species of the genus Magnolia , including M. officinalis , M. obovata , and M. virginiana , has led to the use of supplements prepared from these extracts as anti-depressants, analgesics, aphrodisiacs, and appetite suppressants or stimulants [ 17 ]. Earlier studies [ 24 ] have indicated that 1 and 2 could potentiate γ-aminobutyric acid A (GABA A ) receptors and could act as positive allosteric modulators (PAMs); however, these neolignans have shown no direct interaction with the norepinephrine transporter [ 25 ]. In 2004, Kong et al, evaluated the MAO inhibitory potential of 2 and 3 using rat brain mitochondria; however, no significant rat brain MAO inhibitory activity was noted [ 26 ].…”
Section: Introductionmentioning
confidence: 99%